2013
DOI: 10.1108/01445151311294649
|View full text |Cite
|
Sign up to set email alerts
|

Determining the most probable natural resting orientation of sector shaped parts

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:368933 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Udhayakumar et al [10] determined the most probable natural resting orientation for a family of sector-shaped parts using drop test and theoretical methods (Centroid solid angle method, stability method and critical solid angle method). The effect of initial orientation of the part during drop and height of drop, on the natural resting orientation, was also studied [11].…”
Section: (4)mentioning
confidence: 99%
“…Udhayakumar et al [10] determined the most probable natural resting orientation for a family of sector-shaped parts using drop test and theoretical methods (Centroid solid angle method, stability method and critical solid angle method). The effect of initial orientation of the part during drop and height of drop, on the natural resting orientation, was also studied [11].…”
Section: (4)mentioning
confidence: 99%
“…The orientations a, b and c were considered only for drop tests, and for design of traps, orientations 1 to 8 were considered. Udhayakumar et al (2013) found from the theoretical methods and drop tests that orientation "a" was obtained mostly, irrespective of in which initial orientation the part was Preforming/hot moulding 3…”
Section: Part Consideredmentioning
confidence: 99%
“…Every component will have many orientations. A drop test is used for finding the possible orientations and most probable resting orientation or favorable orientation [8]. This drop test methodology is shown in figure 3.…”
Section: Drop Testmentioning
confidence: 99%